The Influence of Lecturer Servant Leadership, Trust in Lecturers, and Learning Motivation on the Academic Satisfaction of MPI Students at IAIN Takengon - Didi Sartika; Ifnaldi Ifnaldi (Civiliza Publishing, Indonesia., 2026)
This study aims to analyze the influence of Lecturer Servant Leadership, Trust in Lecturer, and Learning Motivation on the Academic Satisfaction of students in the Islamic Education Management (MPI) Study Program, Faculty of Tarbiyah, IAIN Takengon. This study uses a quantitative approach with a survey method. The research sample consisted of 84 students determined using proportional random sampling techniques. Data collection was carried out through the distribution of questionnaires using a Likert scale. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination with the assistance of SPSS. The results of the study indicate that partially, Lecturer Servant Leadership does not have a significant effect on students' academic satisfaction, with a significance value of 0.545 > 0.05. Meanwhile, Trust in Lecturer has a positive and significant effect on academic satisfaction, with a significance value of 0.000 < 0.05. The Learning Motivation variable also has a positive and significant effect on academic satisfaction, with a significance value of 0.000 < 0.05, and is the most dominant variable. Simultaneously, the three independent variables significantly affect students' academic satisfaction, with an F value of 183.613 and a contribution effect of 87.3%. This study emphasizes the importance of building students' trust in lecturers and increasing learning motivation to improve students' academic satisfaction in Islamic higher education institutions.